2010
DOI: 10.1093/aje/kwq005
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of Serum 25-Hydroxyvitamin D Levels During 14 Years in a Population-based Study and During 12 Months in an Intervention Study

Abstract: Low serum 25-hydroxyvitamin D (25(OH)D) levels are associated with risk factors for cardiovascular disease, and they also appear to predict later development of type 2 diabetes, cancer, and an increased mortality rate. These predictions are all based on a single 25(OH)D measurement, but so far there are no known reports on tracking of serum 25(OH)D levels. In the present Norwegian study, serum 25(OH)D levels were measured 1) in 2,668 subjects in the 1994 and 2008 Tromsø surveys and 2) every third month for 1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
204
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(222 citation statements)
references
References 26 publications
14
204
1
3
Order By: Relevance
“…Although repeated measurements are desirable, several cohort studies have shown that 25(OH)D levels remain relatively stable over time. [46][47][48] Lastly, recent study results suggest that levels of the vitamin D-binding protein may affect associations between 25(OH)D and cancer risk. 49,50 Thus, another limitation of our study is that circulating levels of the vitamin D-binding protein were not assayed.…”
Section: Epidemiologymentioning
confidence: 99%
“…Although repeated measurements are desirable, several cohort studies have shown that 25(OH)D levels remain relatively stable over time. [46][47][48] Lastly, recent study results suggest that levels of the vitamin D-binding protein may affect associations between 25(OH)D and cancer risk. 49,50 Thus, another limitation of our study is that circulating levels of the vitamin D-binding protein were not assayed.…”
Section: Epidemiologymentioning
confidence: 99%
“…In Northern Norway at 708 latitude, there is no effective UVB radiation and no cutaneous vitamin D synthesis from October till March (2), and the daily average intake of vitamin D is only 300 IU (3,4). Given that 25-hydroxyvitamin D 3 (25(OH)D 3 ), the metabolite used to evaluate a subject's vitamin D status, has a half-life of 10-40 days (5), one would expect the serum 25(OH)D 3 levels by the end of the UVB winter to be very low. However, data from Tromsø show only a 25% decline during this period (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the few studies that prospectively examined predictors of change in 25(OH)D, predictors included measures of body size [21,22], physical activity [21], vitamin D intake and exogenous estrogen dose [23]. Studies suggest that vitamin D may have implication on the radiographic manifestations of OA [24,25] or cartilage loss in knee joint [26].…”
Section: Discussionmentioning
confidence: 99%